Rotational stability and clinical outcomes after implantation of a new monofocal toric intraocular lens with double C-loop design - Chassain, Christophe; Hallak, Mustafa; Lesaffre, Marc (Journal français d'ophtalmologie, 2023)
Purpose - To investigate rotational stability and visual outcomes of patients unilaterally or bilaterally implanted with a new monofocal toric intraocular lens (IOL). - Setting - Ophthalmology service, clinique Beausoleil, avenue de Lodève, Montpellier. - Design - Single-center retrospective study. - Methods - This study included patients who underwent routine cataract surgery with the PODEYE toric (BVI/PhysIOL SA, Liège, Belgium) IOL using the ZEISS CALLISTO eye®. Biometry and keratometry data, refractive outcomes, rotational stability, and astigmatism correction were recorded. IOL rotation was evaluated using an image analysis technique. Postoperative assessments were performed at 1 week, 1 month, and 4 to 6 months after surgery. - Results - Clinical outcomes of 102 patients (136 eyes) were analyzed. Patients had a mean age of 74 years. Of the included eyes, 25% had an axial length greater than 24.5mm. Median postoperative IOL rotation from baseline (surgery) was 2̊. With the exception of one outlier (15̊ rotation), IOL rotation was ≤ 6̊ (1 month) and ≤ 10̊ (4-6 months) in 100% of the eyes. No surgical IOL re-positioning was required. Median postoperative corrected distance visual acuity was −0.08 logMAR, and median postoperative subjective cylinder was between 0.25 and 0.50 D. - Conclusion - The PODEYE toric IOL showed high rotational stability, allowing for correction of corneal astigmatism during cataract surgery. - Résumé - Objectif - Étudier la stabilité rotationnelle et les résultats visuels de patients implantés avec une nouvelle lentille intraoculaire torique monofocale. - Cadre - Service d’ophtalmologie, clinique Beausoleil, avenue de Lodève, Montpellier. - Conception - Étude rétrospective monocentrique. - Méthodes - Inclusion de patients opérés de cataracte avec implantation du PODEYE torique (BVI/PhysIOL SA, Liège, Belgique) à l’aide du ZEISS CALLISTO eye®. Les données biométriques et kératométriques, les résultats réfractifs, la stabilité rotationnelle et la correction de l’astigmatisme ont été collectés. La rotation de l’IOL a été évaluée à l’aide d’une technique d’analyse d’image. Les évaluations ont été effectuées à 1 semaine, 1 mois et 4 à 6 mois après l’opération. - Résultats - Cent deux patients (136 yeux) ont été analysés. Les patients avaient en moyenne 74 ans, dont 25 % avec une longueur axiale supérieure à 24,5mm. La rotation médiane postopératoire était de 2̊. À l’exception d’un cas (rotation de 15̊), la rotation était ≤ 6̊ (1 mois) et ≤ 10̊ (4-6 mois) dans 100 % des yeux. Aucun implant n’a été repositionné. En postopératoire, l’acuité visuelle de loin corrigée médiane était de −0,08 logMAR, et le cylindre subjectif médian entre 0,25 et 0,50 D. - Conclusion - Le PODEYE torique a montré une grande stabilité rotationnelle, permettant la correction de l’astigmatisme cornéen au décours de la chirurgie de la cataracte.
Online verfügbar: 11. Mai 2023, Artikelversion: 13. Juni 2023
Gesehen am 27.09.2023